Space Adequacy Analysis Based on Population Pressure National park Area (Case Study : Putri Betung Sub District, Gayo Lues, Aceh) - Muhardian, Munar; Rusdi, Muhammad; Karim*, Abubakar (Graduate School of Universitas Syiah Kuala, 2021)
The land requirement for Putri Betung Sub District in Gunung Leuser National Park (GLNP) area kept increasing along with the population growth. The population density in the Putri Betung Sub-district was driven by the need for cultivation and residential area along the GLNP conservation boundary. This study aims to analyze the space adequacy for Putri Betung Sub-District in the GLNP area based on the population pressure prediction for 20 years. The research method was conducted by field survey using remote sensing, interviewed the residents, and analyzed the population pressure index using the Soemarwoto formula. ThePopulation Pressure Index (PPI)forthe cultivation area was determined from 13 villages in Putri Betung Subdistrict and shows that 12 villages had a PPI 1 value (population pressure was over the land carrying capacity limits). Only one village had PPI 1 (population pressure less than the land carrying capacity. Based on data surveys obtained, the cultivation area set in the Putri Betung area was no longer sufficient for population, resultingfrom the expansion in the GLNP area of 4,776.97 ha. Meanwhile, predictive analysis on space adequacy for people living decently in Putri Betung Sub District for 20 upcoming years is 6117.15 ha. In conclusion, 12 out of 13 villages in the Putri Betung SubDistrict havePPI 1 value, which is inversely proportional to the land carrying capacity. The PPI values could result in other pressures on the ecology and biodiversity conservation in National Park. It is suggested that the government need to surpassthe pressure by making new policy on peoples resettlement, expanding the cultivation area, or shifting people's livelihoods.